SIKAP TERHADAP NONMUSLIM DAN LEARNING TO LIVE TOGETHER PADA GURU RAUDHATUL ATHFAL DI KOTA KEDIRI - Fatma Puri Sayekti; Sunarno Sunarno (UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to determine whether there is a relationship between attitudes towards non-Muslims and learning to live together at the teacher Raudhatul Athfal (RA) in Kediri City. The selection of respondents was determined by using a cluster random sampling technique. They are 74 teachers from thirteen RA in Kediri City. The RA is spread over three districts. Collecting data using a questionnaire with a scale of attitudes towards non-Muslims and learning to live together which was developed by the researcher. Based on the Pearson Product Moment correlation analysis, the value is 0.000, which is smaller than 0.05. This means that there is a relationship between attitudes towards non-Muslims and learning to live together on RA teachers in Kediri City. The higher the RA teachers in Kediri City have a positive attitude towards non-Muslims, then they will have better learning to live together. And vice versa. So, to be able to learn to live side by side with a pluralistic society, RA teachers in Kediri City need to develop a positive attitude towards non-Muslims. This will later become an example for RA students to form a similar attitude through preschool education.